An experimental study on single-step dimethyl ether (DME) synthesis from hydrogen and carbon monoxide under various catalysts. (19th October 2015) - Huang, Men-Han; Lee, How-Ming; Liang, Kuo-Chao; Tzeng, Chin-Ching; Chen, Wei-Hsin
Abstract: Dimethyl ether (DME) is a potential and green substitute to diesel and liquefied petroleum gas. In this study, DME synthesized from hydrogen and carbon monoxide (i.e. syngas) through a single step process is investigated to figure out the reaction characteristics. The influences of reaction temperature, H2 /CO molar ratio, and prepared catalyst on DME synthesis are investigated, while the space velocity is fixed at 15, 000 mL (gcat  h) −1 . The results indicate that the optimal reaction temperature for DME synthesis develops at 220 °C where the chemical kinetics and thermodynamic equilibrium are in a comparable state. Increasing H2 /CO ratio increases the CO conversion but lowers the H2 conversion. The maximum DME yield is 2.3 g (gcat  h) −1 which occurs at H2 /CO = 1. The addition of palladium (Pd) into a Cu–ZnO–Al2 O3 catalyst intensifies the CO conversion and DME yield of a gas mixture with syngas and 10 vol% of CO2 . This is the consequence of hydrogen spillover which is able to increase the stability of active Cu against CO2 oxidation. The results also suggest that the dehydration catalyst with higher acidity gives lower DME selectivity and yield. The higher the CO2 concentration in syngas, the lower the CO conversion and DME yield. The present study has provided comprehensive insights into DME synthesis which is conducive to DME production in industry. Highlights: DME synthesis at various operating conditions and physically mixed catalysts is studied. The optimal reaction for maximizing DME yield is 220 °C. The maximum DME yield is 2.3 g (gcat  h) −1  at the H2 /CO ratio of 1. Addition of Pd into a Cu–ZnO–Al2 O3 catalyst can intensify CO conversion and DME yield. The dehydration catalyst with higher acidity gives lower DME selectivity and yield.